Learning Transfer in the Workplace: An Insight Into the Missing Link in the Education and Training of Employees - John Olayemi Okunlola (Studies in Learning and Teaching, 2023)
The goal of education and training is the transfer of learning which requires translating theories to knowledge, skills and learned behaviour. Education can only achieve its intended purpose when theories taught in the classroom are connected to workplace practices. If education and training fail to achieve this lofty objective, then, all efforts, time and resources may be a waste. Transfer of learning only occurs when prior learned knowledge and skills are applied in workplace, either in similar, related, or different contexts. However, there seems to be a missing link in what is being taught and transferred to the workplace in recent times. Aside from the theory of identical elements, this review also considers the theory of near and far transfer. The relevance of these two theories to classroom and workplace is the focal point of this review. Data for this review are secondary sources from documentary reviews, related articles, scholarly works in journals, conference proceedings among others. Data derived from these sources were analysed using content analysis approach. This paper posits that there is a missing link between what is being taught and learnt in the classroom and its workplace application. This paper posits that there is urgent need to make classroom a centre of active learning. Hence, a student-centred pedagogy is recommended, where real-life social contexts are taught in the classrooms, which can ultimately transfer learning to workplace.